GIOS ONLINE PLATFORM AS A TOOL FOR OVERCOMING LEARNING LOSSES IN MATHEMATICS - Daryna V. Vasylieva; Tetiana L. Hodovaniuk (Інформаційні технології і засоби навчання, 2023)
The COVID-19 pandemic worldwide has led to a shift from face-to-face to distance learning. The sudden change in the learning format and the unpreparedness of the education system led to learning losses of students. The most researched and documented learning losses are the ones in mathematics, reading, and science. In Ukraine, face-to-face learning has not fully resumed yet, as a full-scale war broke out after 2 years into the pandemic. Consequently, the problem of overcoming learning losses in mathematics is particularly acute, as the country's economy depends on it in the future. According to the research reviewed in this article, the use of information and communication technologies in the educational process helps to overcome learning losses. These technologies can be used to organize synchronous or asynchronous learning. The article examines the effectiveness of students' independent use of GIOS platform materials to overcome learning losses in mathematics. The results of the entrance and exit tests of students, along with a survey of students and their parents after 1.5 months of independent learning on the platform are described. It is concluded that the independent learning format without a teacher or tutor is not suitable for everyone. Nevertheless, one of the components of overcoming learning losses can be students' independent study of multimedia materials. It has been found that the older students are, the more effective this kind of learning is. Based on a survey of students, the characteristics of the GIOS platform that motivated students to learn and helped them to understand the material were identified. Among the characteristics are: the integrity of the course, elements of gamification, the availability of theoretical material in several forms (videos, schemes, examples of solved tasks), the ability to view it several times and return at any time, the availability of training tasks, tasks of different levels and formats (including non-standard ones), the ability to review the covered materials to analyze errors, the ability to improve results by solving similar tasks. It is noted that in order to help their students overcome learning losses, teachers should either develop mathematics materials independently or use ready-made materials.